Pré-dimensionamento de lodos ativados com aeração prolongada (LAAP) para tratamento de água residuária da indústria cervejeira - Coutinho, Emanuel Sene (2024)
The <Design of the Extended Aeration Activated Sludge System (EAAS) for Brewery Wastewater Treatment" highlights the importance of efficient planning to address the environmental challenges caused by large-scale production and the variety of industrial wastewater. The study aimed to size the system, adapting domestic sewage treatment criteria to the needs of the brewery industry, in accordance with Brazilian legislation. The main sized components include a grit chamber with an area of 0.53 m2 and a volume of 0.37 m3, an equalization tank with a total volume of 544.42 m3, a biological reactor with a volume of 2419.98 m3, a secondary clarifier with an area of 38.87 m2 and a volume of 77.74 m3, and a final clarifier with a final area of 33.18 m2 and a final volume of 99.54 m3. In the end, it was determined that the adoption of EAAS technology for treating wastewater from the brewery industry is a viable alternative, based on a comparative analysis involving calculations and a review of preexisting studies.